CONCEPTION OF ECOLOGY AS THE SUBJECT OF PROGRESSIVE LAW AND THE EMBODIMENT OF INTER-GENERATION JUSTICE - Vincentius Patria Setyawan (Domus Legalis Cogitatio, 2024)
The unfinished discussion regarding progressive law is the subject of progressive law. Progressive law pays attention to the human aspects of judging and providing protection for entities that are "those who are weak" and need protection. Ecology is included in entities that require protection, so it has the potential to be conceptualized as a progressive legal subject. This article will analyze the potential of ecology as a subject of progressive law associated with the realization of inter-generational justice. The research method used in writing this article is a normative legal research method with a conceptual approach. The results of the analysis in this article show that ecology can be conceptualized as a progressive legal subject and in accordance with the embodiment of intergenerational justice. Ecology is not only needed by this generation but also needed by future generations.